Binding of Mycobacterium tuberculosis to complement receptor type 3 expressed in mammalian cells : dependence on serum opsonins - Cywes, Colette (Division of Medical Biochemistry and Structural Biology, 2017)
Nonopsonic invasion of mononuclear phagocytes by Mycobacterium tuberculosis (M. tb.) is likely important in the establishment of a primary infection in the lung. M. tb. binds to a variety of phagocyte receptors, of which the mannose receptor and the complement receptor type 3 (CR3) may support nonopsonic binding. CR3, a β₂ integrin, is a target for diverse intracellular pathogens, but its role in nonopsonic binding remains uncertain. We have examined the binding of M. tb. to human CR3 heterologously expressed in Chinese hamster ovary (CHO) cells, thereby circumventing the problems of competing receptors and endogenously synthesised complement, which are inherent in studies with mononuclear phagocytes. The surface expression and functional activity of CR3 were confirmed by rosetting with beads coupled to anti-CR3 monoclonal antibodies (MAbs) and with C3bi-coated microspheres, respectively. We found thatM. tb. binds 4-7-fold more avidly to CR3- expressing CHO cells than to wild-type cells, and importantly, that this binding is very similar in the presence of fresh or heat-inactivated human or bovine sera, or no serum. The binding of M. tb. to the transfected CHO cells is CR3-specific, as it is inhibited by anti-CDllb and anti-CD18 MAbs; interestingly, binding is not inhibited by a MAb (2LPM19c) specific for the C3bi-binding site on CDI lb. Electron micrographs of infected CR3-expressing CHO cells reveal the presence of intracellular bacteria enclosed in well-defined, membrane-bound vacuoles. We conclude that the binding of M. tb. to CR3 is nonopsonic and that the organism likely expresses a ligand that directly binds to CR3.